A random PWM technique for Z-source inverter based on pseudorandom binary sequence bits - Bhuvanasundaram, Sambasivam; Vagapov, Yuriy; Lupin, Sergey; Chakirov, Roustiam (2015 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference (EIConRusNW), 2015)
The paper analyses a random pulse width modulated technique applicable for Z-source inverter. The proposed technique comprises the random pulse position PWM with a randomised frequently triangular carrier having characteristics of both space vector and random lead-lag modulations. This random pulse PWM is produced through the logical comparison of the pseudorandom binary sequence bits with the PWM pulses corresponding to two fixed frequency triangular carriers. Matlab/Simulink was used for modelling and simulation of the proposed method. It has been found that the output harmonic spectra of a Z-source inverter operating under the PWM with randomised frequency are dispersed and continuously distributed that can significantly reduce acoustic noise generated by the inverter and the load.